solve the logarithmic equation [tex] log_{3} {x}^{2} – log_{3}(x + 6) = 1[/tex] ​

Question

solve the logarithmic equation
[tex] log_{3} {x}^{2} – log_{3}(x + 6) = 1[/tex]

in progress 0
Doris 1 year 2021-08-01T22:53:41+00:00 2 Answers 7 views 0

Answers ( )

    0
    2021-08-01T22:55:01+00:00

    Answer:

    Step-by-step explanation:

    Using log(x) – log(y) = log (x/y)

    logx^2 – log(x+6) = 1 is equal to:

    log (x^2/(x+6)) = 1

    Taking inverse base 3 log on both side:

    x^2/(x+6) = 3

    x^2 = 3x + 18

    x^2 – 3x – 18 = 0

    (x-6)(x+3) = 0

    x = 6 or -3

    0
    2021-08-01T22:55:15+00:00

    Answer:

    Step-by-step explanation:

    1 = base 3log3

    substitute

    logx^2-log(x+6) = log3

    logx^2 – log(x+6) – log3 = 0

    log( (x^2/(x+6))/3 ) = 0

    anti-log

    x^2/3(x+6) = 1

    x^2 = 3(x+6)

    x^2-3x-18=0

    x=6 n -3

    anti-log base 3 on both sides:

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )